EMPLOYEE EXPERIENCE: PEOPLE MANAGEMENT MODEL IN THE KNOWLEDGE ECONOMY - López Gómez, Josefa Elisa; Pascual Pedraza, José Luis; Parrilla Martínez, Antonio (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
We are immersed in the so-called knowledge economy, caused among other aspects by the possibilities that digital transformation offers us and in this economic context there are two fundamental parameters for the management of organizations, the first is the degree of digitization of the activities that are carried out and the second is the awareness that the differential value of these digitized companies is the human talent they can count on and that can make the difference between successful organizations and those that will not.The importance of talent in this environment is key and it has become a rare commodity that must be taken care of, which is why people management is highly critical within companies and the focus on management must be focused in making real this differential value that individuals can contribute, listening to their needs and creating relationship models that are adapted and consistent with the DNA of the companies. For this, the Employee Experience model has emerged.In order to achieve adequate results, organizations have to adapt their people management models to the new economic reality, creating management models focused on providing them with adequate support, turning employees into internal customers and making them live the best of experiences.The purpose of this article is to expose both conceptually and through concrete data how the management model focused on the employee experience can help meet the challenges of our organizations, both private and public, in terms of people management.Within the framework of the Public Administration and, more specifically in the Civil Guard, the model proposed here can provide objective data that provide valuable information for decision-making in people management.
Keywords: Knowledge Economy; Management model; People Analytics; Talent; Commitment; Employee Experience; leadership; eNPS; Public Administration; Civil Guard